2023
DOI: 10.4102/phcfm.v15i1.4188
|View full text |Cite
|
Sign up to set email alerts
|

Self-care behaviours and practices of professional nurses working in primary health care clinics

Mukelani L. Muhlare,
Charlene Downing

Abstract: Background: Historically, the nursing profession focused on caring for patients, families and communities but neglected aspects of self-care. Self-care is essential for nurses, as it could impact the quality of care nurses render to patients.Aim: This article investigated professional nurses’ self-care behaviours and practices in primary health care clinics.Setting: The study was conducted at selected primary health care facilities (clinics) in regions C and D of the city of Johannesburg, Gauteng.Methods: A cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“… 11 12 Nurses frequently neglect self-care and prioritise the well-being and care of their patients. 13 14 A cross-sectional study revealed that more than half of nurses did not engage in health-promoting self-care. 15 Nurses encounter numerous barriers to self-care, such as shift work, hectic schedules, competing time demands, cost considerations, limited resource availability and work-related stress.…”
Section: Introductionmentioning
confidence: 99%
“… 11 12 Nurses frequently neglect self-care and prioritise the well-being and care of their patients. 13 14 A cross-sectional study revealed that more than half of nurses did not engage in health-promoting self-care. 15 Nurses encounter numerous barriers to self-care, such as shift work, hectic schedules, competing time demands, cost considerations, limited resource availability and work-related stress.…”
Section: Introductionmentioning
confidence: 99%